Factors associated with nurses’ perceptions about quality of end-of-life care - Hussin, Emni Omar Daw; Wong, Li Ping; Chong, Mei Chan; Subramanian, Pathmawathi (Wiley, 2018)
Aim: To examine the factors associated with nurses’ perceptions of the quality of end-of-life care. Background: With increasing demand for hospitals to provide end-of-life care, the low quality of palliative care provided in hospital settings is an issue of growing concern in developing countries. Most dying patients receive their care from general nurses, irrespective of the nurses’ specialty or level of training. Method: A structured cross-sectional questionnaire survey was conducted of 553 nurses working at a teaching hospital in Malaysia. Results: The mean scores for nurses’ knowledge about end-of-life care, their attitudes towards end-of-life care and the perceived quality of end-of-life care were low. The factors identified as significantly associated with the quality of end-of-life care were nurses’ levels of knowledge and their attitudes towards end-of-life care. Discussion: Factors that contributed to the low quality of end-of-life care were inadequate knowledge and negative attitudes. These findings may reflect that end-of-life care education is not well integrated into nursing education. Conclusion: The findings of this study suggest that there is a need to increase the nurses’ level of knowledge and improve their attitude towards end-of-life care in order to enhance the quality of care provided to dying patients. Implications for nursing and health policy: Nurse managers and hospital policymakers should develop strategies to enhance nurses’ level of knowledge, as well as providing adequate emotional support for nurses who care for dying patients and their families. Nurses should be proactive in increasing their knowledge and adopting more positive attitudes towards end-of-life care.